2011
DOI: 10.1007/s12598-011-0363-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TGO growth in thermal barrier coatings using impedance spectroscopy

Abstract: Impedance spectroscopy was employed to evaluation of TGO growth on the interface of YSZ/bond coat in plasma sprayed thermal barrier coatings during isothermal oxidation and exposed to Na 2 SO 4 at 950 ºC. Various observed electrical responses relating to the thickness, continuous nature and purity of the TGO layer were explained using an equivalent circuit model. The results show the thickness of TGO increases with exposure time. The TGO after isothermal oxidation mainly contains Al 2 O 3 . However, the TGO af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…[1,3,4], which makes the performance of TBCs unsatisfactory. As a result, the wide application of TBCs has been entitled to advanced nondestructive test (NDT) techniques for evaluation and failure detection during service [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[1,3,4], which makes the performance of TBCs unsatisfactory. As a result, the wide application of TBCs has been entitled to advanced nondestructive test (NDT) techniques for evaluation and failure detection during service [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Since TGO growth rates related to the square root of time [23], the thickness of TGO in the cycle 60, is determined by the equation. 3:…”
Section: Calculating Coating Parametersmentioning
confidence: 99%
“…When the coating undergoes multiple thermal cycles, thermal mismatch stress (σ t ) will be induced due to the different thermo-mechanical properties between the layers [26]. Many research results have indicated that TGO growth at high temperatures is one of the critical causes affecting the coating failure [27,28]. Ceramic sintering at high temperatures is another key factor for coating degradation and delamination [29,30].…”
Section: Introductionmentioning
confidence: 99%